A full-hydrophobic friction-resistant structural material and a preparation method thereof
Patent Information
- Application Number
- CN202410741524.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-06-11
AI Technical Summary
[0003]针对超疏水材料在摩擦、结冰、撞击等测试中会失效的问题,本发明通过将低表面化学物质修饰具有多孔结构的材料,最终获得全疏水耐摩擦的功能
[0036]1.本发明通过对低表面化学物质修饰具有多孔结构的材料,经过氟化处理,不仅可以使多孔结构表面获得超疏水功能,其内部也同样被疏水修饰改性,获得了全疏水结构材料。
Smart Images

Figure CN118745118B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology, specifically relating to a fully hydrophobic structural material with anti-icing, high-temperature resistance, and friction resistance, and its preparation method. Background Technology
[0002] Currently, research on hydrophobic materials mainly focuses on superhydrophobic materials, primarily through the preparation of micro / nano structures and the modification of low-surface-energy chemicals on the material surface to ultimately obtain superhydrophobic materials. Because the surface tension of droplets on superhydrophobic surfaces causes them to exist in a near-spherical shape, resulting in a very small solid-liquid contact area, this surface also has a function of delaying freezing in low-temperature environments, and is therefore used as an anti-icing material. However, after continuous water impacts or surface freezing, the superhydrophobic surface will suffer excessive stress leading to the destruction of the microstructure, ultimately losing its superhydrophobic function. This is why artificial superhydrophobic materials are difficult to maintain their function for a long time in natural environments. Existing researchers have improved the durability of superhydrophobic materials to some extent by designing metal frameworks with good mechanical properties to protect the nanostructures. However, once the surface is damaged, the superhydrophobic function will still be lost. Therefore, research on fully hydrophobic materials is crucial for improving the performance stability of superhydrophobic materials in harsh environments and is an effective method to solve the stability problem of hydrophobic materials. Summary of the Invention
[0003] To address the issue of superhydrophobic materials failing in tests such as friction, icing, and impact, this invention modifies a porous material with low surface chemical composition to achieve a fully hydrophobic and friction-resistant finish. After friction and icing tests, the superhydrophobic function was found to remain intact; the chemical composition of the internal and surface components did not change significantly.
[0004] In a first aspect, the present invention provides a fully hydrophobic and friction-resistant structural material, which is obtained by fluorination of porous oxides, thereby achieving the functions of friction resistance and anti-icing.
[0005] The porous oxide is selected from one or more of zinc oxide, magnesium oxide, aluminum oxide, and silicon dioxide.
[0006] Preferably, the porous oxide has a particle size of 10 nm to 1 mm.
[0007] The porous oxide has a pore size of 2nm-100nm and a porosity of 10-60%.
[0008] The fluorination treatment refers to contacting a porous oxide with a fluorinating agent, heating it, and causing the fluorinating agent to vaporize, thereby causing a reaction between the surface and internal structure of the porous oxide to obtain a fully hydrophobic and friction-resistant structural material.
[0009] The fluorinating agent is a fluoroalkylsilane.
[0010] The mass ratio of the fluorinating agent to the porous oxide is 1:(10-50).
[0011] Traditional liquid immersion fluorination processes cannot achieve sufficient wetting of the pores and result in varying fluorinating agent concentrations at different locations within the pores, leading to uneven fluorination and consequently poor abrasion resistance and hydrophobicity of the material. This invention addresses this issue by heating and vaporizing the fluorinating agent, allowing it to penetrate evenly and uniformly into the depths of the pores. The vaporization process ensures a consistent fluorinating agent concentration, achieving comprehensive and uniform fluorination of both the internal and external layers of the porous material, thereby improving its superhydrophobic properties.
[0012] Preferably, the fluoroalkylsilane is a combination of small-molecule polyfluorosilanes with ≤6 carbon atoms and large-molecule polyfluorosilanes with ≥12 carbon atoms.
[0013] More preferably, the macromolecular polyfluorosilane accounts for 70-90 wt% of the total fluoroalkylsilane.
[0014] The small molecule polyfluorosilane is selected from trimethylfluorosilane ((CH3)3SiF) and diethyldifluorosilane (C4H). 10 F2Si), (trifluoromethyl)trimethylsilane (C4H9F3Si) or ethyltrifluorosilane.
[0015] The macromolecular polyfluorosilane is heptadecafluorodecyltrimethoxysilane (C 13 H 13 F 17 O3Si).
[0016] Typically, fluorosilanes such as heptadecafluorodecyltrimethoxysilane have good hydrophobic effects and are often used for surface hydrophobic modification. However, due to the small pore size of porous oxides, the efficiency of heptadecafluorodecyltrimethoxysilane entering the interior of porous oxides after vaporization is limited when used alone, resulting in incomplete hydrophobic modification. Therefore, this invention adds a small-molecule polyfluorosilane, which not only allows the large-molecule polyfluorosilane heptadecafluorodecyltrimethoxysilane with hydrophobic properties to uniformly enter the deep pore structure, but also simultaneously performs surface hydrophobic modification, improving the efficiency of internal-surface hydrophobic modification of porous materials and obtaining a fully hydrophobic structure material.
[0017] Furthermore, 70-90% macromolecular polyfluorosilanes and 10-30% small molecule polyfluorosilanes, through the combination of different silanes and the synergistic ratio of the two, facilitate the formation of a modified multi-level framework structure inside the pores of porous oxides, enhancing the mechanical strength of porous oxides, making them less prone to collapse and damage, and resulting in stronger stability of the fully hydrophobic material.
[0018] Secondly, this application provides a method for preparing a fully hydrophobic and friction-resistant structural material, comprising the following steps:
[0019] 1) Mix the oxide with the pore-forming agent and calcine at high temperature to obtain porous oxide.
[0020] The oxide is selected from one or more of zinc oxide, magnesium oxide, aluminum oxide, and silicon dioxide.
[0021] The pore-forming agent is selected from one or more of graphite, polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), and polyvinylidene fluoride (PVDF).
[0022] The pore-forming agent and the porous oxide are mixed in a mass ratio of 1:(10-100).
[0023] The high-temperature calcination temperature is 500-1200℃, and the calcination time is 5-30 minutes.
[0024] Optionally, hot pressing is performed before high-temperature calcination, with the following conditions: 10-20 atmospheres, 200-300℃, and 10-60 minutes.
[0025] 2) Fluoride treatment of porous oxides yields a fully hydrophobic and friction-resistant structural material.
[0026] The fluorination treatment refers to contacting (mixing) a fluorinating agent with a porous oxide, heating it to vaporize the fluorinating agent, and modifying both the surface and interior of the porous oxide with hydrophobic fluorination to obtain a fully hydrophobic and friction-resistant structural material.
[0027] The fluorinating agent is a fluoroalkylsilane.
[0028] The amount of fluorinating agent added is such that the mass ratio of fluorinating agent to porous oxide is 1:(10-50).
[0029] Preferably, the fluoroalkylsilane is a small-molecule polyfluorosilane with ≤6 carbon atoms or a large-molecule polyfluorosilane with ≥12 carbon atoms.
[0030] More preferably, the macromolecular polyfluorosilane accounts for 70-90 wt% of the total fluoroalkylsilane.
[0031] The small molecule polyfluorosilane is selected from trimethylfluorosilane ((CH3)3SiF) and diethyldifluorosilane (C4H). 10 F2Si), (trifluoromethyl)trimethylsilane (C4H9F3Si) or ethyltrifluorosilane.
[0032] The macromolecular polyfluorosilane is heptadecafluorodecyltrimethoxysilane (C 13 H 13 F 17O3Si).
[0033] The heating temperature is 80-120℃, and the heating time is 5-8 hours.
[0034] During the heating process of fluorinated reagents, small-molecule polyfluorosilanes can rapidly enter the pores of porous oxides, while large-molecule polyfluorosilanes vaporize and enter the interior and surface of the porous structure. This ensures that the hydrophobic polyfluorosilanes can uniformly penetrate deep into the pore structure and simultaneously perform surface hydrophobic modification, improving the efficiency of internal and surface hydrophobic modification of porous materials and achieving a fully hydrophobic structure. Furthermore, the addition of different types of fluorinated silane hydrophobic materials can form a modified multi-level framework structure inside the pores, improving the mechanical properties and stability of the porous material, thereby exhibiting properties such as abrasion resistance, anti-icing, and weather resistance.
[0035] The beneficial effects of this invention are:
[0036] 1. This invention modifies porous materials with low surface chemical substances and then fluorinates them, which not only gives the porous surface superhydrophobic properties, but also modifies the interior to be hydrophobic, resulting in a fully hydrophobic material.
[0037] 2. This invention uses modified fluorinating agents and different types of fluorosilanes to uniformly penetrate deep into the pore structure while performing surface hydrophobic modification, thereby improving the efficiency of internal-surface hydrophobic modification of porous materials and realizing fully hydrophobic structural materials. At the same time, due to the addition of different hydrophobic materials, a modified multi-level framework structure is formed inside the pores, which improves the mechanical properties and stability of porous materials, thus giving them advantages such as friction resistance, anti-icing, and weather resistance.
[0038] 3. The fully hydrophobic and friction-resistant structural material prepared by this invention retains its superhydrophobic function after friction and icing tests; the chemical composition of the internal and surface remains largely unchanged. After more than 100 cycles of in-situ icing, the contact angle does not change significantly, maintaining its superhydrophobicity. It exhibits high friction resistance, withstanding 300 cycles of friction without structural damage. Even under long-term friction (more than 400 cycles), even with slight damage to the external structure, the exposed surface remains superhydrophobic, thus remaining a fully hydrophobic material. Attached Figure Description
[0039] Figure 1 This is a schematic diagram of the preparation process of the fully hydrophobic and friction-resistant structural material of the present invention.
[0040] Figure 2The following are images of the fully hydrophobic, wear-resistant, and superhydrophobic structural material and its performance testing in Embodiment 1 of the present invention: a) is an electron microscope image of the surface of the fully hydrophobic, wear-resistant, and superhydrophobic structural material; b) is an image of the fully hydrophobic, wear-resistant, and superhydrophobic structural material undergoing a friction test; and c) is an image showing the changes in the contact angle and roll-off angle of the fully hydrophobic, wear-resistant, and superhydrophobic structural material during 1-6 friction cycles.
[0041] Figure 3 This is a schematic diagram illustrating the hydrophobic effect of the fully hydrophobic and friction-resistant zinc oxide structure prepared in Example 1.
[0042] Figure 4 This is a schematic diagram illustrating the hydrophobic effect of the fully hydrophobic and friction-resistant magnesium oxide structure prepared in Example 2. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0044] Example 1
[0045] A fully hydrophobic and friction-resistant structural material and its preparation method include the following steps:
[0046] 1) Mix the oxide with a pore-forming agent and calcine at high temperature to obtain a porous oxide;
[0047] Zinc oxide and graphite were mixed in a mass ratio of 50:1, then heated to 1000°C in a muffle furnace and held for 5 minutes. After cooling, the muffle furnace was opened to allow air to pass through, then closed and reheated until all the graphite inside had disappeared, thus obtaining porous zinc oxide.
[0048] 2) Fluoride treatment of porous oxides yields a fully hydrophobic and friction-resistant structural material.
[0049] 10 mL of commercially available heptadecafluorodecyltrimethoxysilane FAS-17 and 50 g of the porous zinc oxide sample obtained in step 1) were placed in a vacuum desiccator, heated to 90 °C, and maintained for 6 hours to obtain a fully hydrophobic and abrasion-resistant zinc oxide structure. The preparation process is as follows: Figure 1 As shown.
[0050] The surface electron microscope image of the fully hydrophobic and friction-resistant zinc oxide structure obtained in Example 1 is shown below. Figure 2 As shown in a). The fully hydrophobic, abrasion-resistant zinc oxide structure was subjected to a friction test (e.g., ...). Figure 2 As shown in b), observe the effects of the material's contact angle and roll-off angle, such as Figure 2As shown in c), after 1-6 friction cycles, the contact angle and roll-off angle of the material change very little, indicating that the frictional force has no significant effect on its contact angle and roll-off angle. This demonstrates that the superhydrophobicity of the material remains unchanged, and it retains its full superhydrophobicity even after multiple friction cycles, indicating good wear resistance. The hydrophobic properties of the fully hydrophobic friction-resistant zinc oxide structure obtained in Example 1 are as follows: Figure 3 As shown, the zinc oxide with a fully hydrophobic and friction-resistant structure in Example 1 has good hydrophobic properties.
[0051] Example 2
[0052] A fully hydrophobic and friction-resistant structural material and its preparation method include the following steps:
[0053] 1) Mix the oxide with a pore-forming agent and calcine at high temperature to obtain a porous oxide;
[0054] Magnesium oxide and PMMA were mixed in a mass ratio of 20:1, then heated to 500°C in a muffle furnace and held for 5 minutes. After cooling, the muffle furnace was opened, closed, and then reheated. Porous zinc oxide was obtained after all the internal carbides had disappeared.
[0055] 2) Fluoride treatment of porous oxides yields a fully hydrophobic and friction-resistant structural material.
[0056] 100g of the porous magnesium oxide sample obtained in step 1) was placed in a vacuum desiccator and heated to 90℃ for 6 hours using 10mL of heptadecafluorodecyltrimethoxysilane FAS-17 to obtain a fully hydrophobic and abrasion-resistant magnesium oxide structure. The hydrophobic properties of this material are as follows: Figure 4 As shown, the magnesium oxide with the fully hydrophobic and friction-resistant structure has good hydrophobic properties.
[0057] Example 3
[0058] A fully hydrophobic and friction-resistant structural material and its preparation method include the following steps:
[0059] 1) Mix the oxide with the pore-forming agent and calcine at high temperature to obtain a porous oxide: the same as step 1) in Example 1.
[0060] 2) Fluoride treatment of porous oxides yields a fully hydrophobic and friction-resistant structural material.
[0061] 8 mL of heptadecafluorodecyltrimethoxysilane FAS-17, 2 mL of (trifluoromethyl)trimethylsilane C4H9F3Si, and 100 g of the porous zinc oxide sample obtained in step 1) were placed in a vacuum desiccator, heated to 90 °C, and kept for 6 hours to obtain zinc oxide with a fully hydrophobic and abrasion-resistant structure.
[0062] Example 4
[0063] A fully hydrophobic and friction-resistant structural material and its preparation method include the following steps:
[0064] 1) Mix the oxide with the pore-forming agent and calcine at high temperature to obtain a porous oxide: the same as step 1) in Example 2.
[0065] 2) Fluoride treatment of porous oxides yields a fully hydrophobic and friction-resistant structural material.
[0066] The following were used: 8 mL of heptadecyltrimethoxysilane FAS-17 and 2 mL of triethyl(trifluoromethyl)silane C7H 15 100g of the porous magnesium oxide sample obtained from F3Si and step 1) was placed in a vacuum dryer, heated to 90℃, and kept for 6 hours to obtain magnesium oxide with a fully hydrophobic and friction-resistant structure.
[0067] Example 5
[0068] A fully hydrophobic and friction-resistant structural material and its preparation method include the following steps:
[0069] 1) Mix the oxide with a pore-forming agent and calcine at high temperature to obtain a porous oxide;
[0070] Silica and PVDF were mixed at a mass ratio of 60:1, then heated to 800°C in a muffle furnace and held for 5 minutes. After cooling, the muffle furnace was opened, closed, and then heated again. Porous silica was obtained once all the internal carbides had disappeared.
[0071] 2) Fluoride treatment of porous oxides yields a fully hydrophobic and friction-resistant structural material.
[0072] 8 mL of heptadecafluorodecyltrimethoxysilane FAS-17, 2 mL of (trifluoromethyl)trimethylsilane C4H9F3Si, and 200 g of the porous silica sample obtained in step 1) were placed in a vacuum desiccator, heated to 100 °C, and kept for 5 hours to obtain a fully hydrophobic and abrasion-resistant silica structure.
[0073] Comparative Example 1
[0074] A superhydrophobic structural material and its preparation method, comprising the following steps:
[0075] 10 mL of heptadecafluorodecyltrimethoxysilane FAS-17 and 100 g of zinc oxide sample were placed in a vacuum desiccator, heated to 90 °C, and held for 6 hours to obtain zinc oxide with a superhydrophobic surface modified structure.
[0076] Performance Test 1: Friction Resistance
[0077] The materials prepared in the examples and comparative examples were tested for abrasion resistance. Under different test pressure conditions, after different number of abrasion cycles, the destructiveness and integrity of the materials were observed. The data results are shown in Table 1.
[0078] Table 1
[0079]
[0080]
[0081] Performance Test 2: Superhydrophobic Performance
[0082] The fully hydrophobic wear-resistant structural materials prepared in the examples and comparative examples were subjected to 100 cycles of friction at room temperature and pressure. The changes in contact angle and hydrophobicity were then measured. The results are shown in Table 2.
[0083] Table 2
[0084] Example 1 100 times <3° Superhydrophobic Example 2 100 times <3° Superhydrophobic Example 3 100 times 1° Superhydrophobic Example 4 100 times 1° Superhydrophobic Example 5 100 times 2° Superhydrophobic Comparative Example 1 100 times 5° Non-hydrophobic
[0085] As shown in Tables 1-2, the fully hydrophobic friction-resistant structural material of the present invention has hydrophobic modification effects on both the internal and external surfaces, and also exhibits excellent friction resistance and compressive strength. The fully hydrophobic friction-resistant structural material prepared in the examples maintains structural integrity after 200 cycles of friction, and the superhydrophobic structure remains unchanged. When the number of friction cycles increases to 300-400 cycles, although some material surfaces show slight damage, the superhydrophobic properties are still present due to the uniform hydrophobic treatment within the porous structure.
[0086] The data from Examples 1 and 3, and Examples 2 and 4 show that the addition of small molecule fluoroalkanes can improve the hydrophobic modification effect inside the pores of porous materials. At the same time, the addition of different fluorosilanes can also improve the overall mechanical properties of porous materials. The fully hydrophobic wear-resistant materials of Examples 3 and 4 were not damaged on the surface and inside after 400 cycles of friction, further improving the material's friction resistance and anti-icing advantages, and has a wider application potential.
[0087] The porous material in Comparative Example 1 has an insufficient pore structure and channels, so the hydrophobic modifying agent cannot enter the pores and mainly forms a hydrophobic layer on the surface. Therefore, if the material is damaged, the exposed part will not be hydrophobically modified, that is, it will not have hydrophobic function.
[0088] The above-described embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and are not intended to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of protection of the claims.
Claims
1. A fully hydrophobic and friction-resistant structural material, characterized in that, The porous oxide is contacted with a fluorinating agent and heated. The porous oxide is then fluorinated to obtain the fully hydrophobic and abrasion-resistant structural material. The porous oxide is selected from one or more of zinc oxide, magnesium oxide, aluminum oxide, and silicon dioxide; The fluorinating agent is a fluoroalkylsilane; The mass ratio of the fluorinating agent to the porous oxide is 1:(10-50); The fluoroalkylsilane is a combination of small-molecule polyfluorosilanes with C ≤ 6 carbon atoms and large-molecule polyfluorosilanes with C ≥ 12 carbon atoms. Macromolecular polyfluorosilanes account for 70-90 wt% of the total fluoroalkylsilanes.
2. The fully hydrophobic and friction-resistant structural material according to claim 1, characterized in that, The porous oxide has a particle size of 10 nm to 1 mm. The porous oxide has a pore size of 2nm-100nm and a porosity of 10-60%.
3. The fully hydrophobic and friction-resistant structural material according to claim 1, characterized in that, The small molecule polyfluorosilane is selected from trimethylfluorosilane ((CH3)3SiF) and diethyldifluorosilane (C4H). 10 F2Si), (trifluoromethyl)trimethylsilane (C4H9F3Si) or ethyltrifluorosilane; The macromolecular polyfluorosilane is heptadecafluorodecyltrimethoxysilane.
4. A method for preparing a fully hydrophobic and friction-resistant structural material, characterized in that, Includes the following steps: (1) Mix the oxide with the pore-forming agent and calcine at high temperature to obtain porous oxide; (2) Fluoride treatment of porous oxides to obtain a fully hydrophobic and friction-resistant structural material; The oxide is selected from one or more of zinc oxide, magnesium oxide, aluminum oxide, and silicon dioxide; The fluorination treatment in step (2) refers to contacting the porous oxide with a fluorinating agent, heating it, and causing the fluorinating agent to vaporize, so that the surface and interior of the porous oxide are modified by fluorination and hydrophobicity. The fluorinating agent is a fluoroalkylsilane; The mass ratio of the fluorinating agent to the porous oxide is 1:(10-50); The fluoroalkylsilane is a combination of small-molecule polyfluorosilanes with C ≤ 6 and large-molecule polyfluorosilanes with C ≥ 12, wherein the large-molecule polyfluorosilane accounts for 70-90 wt% of the total fluoroalkylsilane.
5. The preparation method according to claim 4, characterized in that, The pore-forming agent in step (1) is selected from one or more of graphite, polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), and polyvinylidene fluoride (PVDF); the mass ratio of the pore-forming agent to the oxide is 1:(10-100); The high-temperature calcination temperature is 500-1200℃, and the calcination time is 5-30 minutes.
6. The preparation method according to claim 4, characterized in that, The heating temperature in step (2) is 80-120℃ and the heating time is 5-8 hours.
7. The preparation method according to claim 4, characterized in that, The small molecule polyfluorosilane is selected from trimethylfluorosilane, diethyldifluorosilane, (trifluoromethyl)trimethylsilane or ethyltrifluorosilane; The macromolecular polyfluorosilane is heptadecafluorodecyltrimethoxysilane.
Citation Information
Patent Citations
Glasses lens with anti-sliding protective layer and preparation method thereof
CN108508508A
Preparation and application of high-stability cuprous modified mesoporous oxide material
CN110314643A
